231k views
1 vote
____Zn(s) + ____HCl(aq) → ____ZnCl2(s) + ____H2(g)

User Eclectic
by
5.1k points

1 Answer

3 votes

Hey there!

Assuming you want us to balance the equation:

Zn + HCl → ZnCl₂ + H₂

Balance Zn.

1 on the left, 1 on the right. Already balanced.

Balance H.

1 on the left, 2 on the right. Add a coefficient of 2 in front of HCl.

Zn + 2HCl → ZnCl₂ + H₂

Balance Cl.

2 on the left, 2 on the right. Already balanced.

Our final balanced equation:

Zn + 2HCl → ZnCl₂ + H₂

Hope this helps!

User JakeParis
by
4.8k points